2021
DOI: 10.3389/fimmu.2021.625297
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Immunity, and Microbiota Interactions: An Integrative Analysis of the Intestine Transcriptional Response and Microbiota Modulation in Gilthead Seabream (Sparus aurata) Fed an Essential Oils-Based Functional Diet

Abstract: Essential oils (EOs) are promising alternatives to chemotherapeutics in animal production due to their immunostimulant, antimicrobial, and antioxidant properties, without associated environmental or hazardous side effects. In the present study, the modulation of the transcriptional immune response (microarray analysis) and microbiota [16S Ribosomal RNA (rRNA) sequencing] in the intestine of the euryhaline fish gilthead seabream (Sparus aurata) fed a dietary supplementation of garlic, carvacrol, and thymol EOs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 98 publications
0
20
1
Order By: Relevance
“…In addition, the above-mentioned study revealed that the tested phytogenic compounds promoted the presence of sialic-acids containing glycoproteins in both epithelial and mucous cells, which globally resulted in a decrease in the intensity of gills' infestation by the monogenean ectoparasite Sparicotyle chrysophrii in gilthead seabream (15). Both, referred phytogenics combinations were observed to positively affect the gut health status of those fish species by improving the protective intestine mucus coverage post-challenge ( 13), regulating the intestine immune transcription (12) and modulating their intestinal microbiota (12,105).…”
Section: Effect Of Combinations Of Phytogenicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the above-mentioned study revealed that the tested phytogenic compounds promoted the presence of sialic-acids containing glycoproteins in both epithelial and mucous cells, which globally resulted in a decrease in the intensity of gills' infestation by the monogenean ectoparasite Sparicotyle chrysophrii in gilthead seabream (15). Both, referred phytogenics combinations were observed to positively affect the gut health status of those fish species by improving the protective intestine mucus coverage post-challenge ( 13), regulating the intestine immune transcription (12) and modulating their intestinal microbiota (12,105).…”
Section: Effect Of Combinations Of Phytogenicsmentioning
confidence: 99%
“…Phytogenic administration has the potential to regulate the mucosal barrier function by means of several molecular mechanisms, in which the phytogenic bioactive compounds interact with cellular transcription factors and metabolic cascades. Therefore, the modulation of the expression of genes coding for immune relevant molecules alter the mucosal protective characteristics and their immunological status (12)(13)(14)(15)(16). Besides, the immune system influences the regulation and composition of the microbiota and vice versa, an interaction that plays a determinant role in the maintenance of the mucosal integrity and functionality (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils are added to feed and water as taste enhancers, and they are also administered to boost immunity and improve the performance of poultry [16,21]. − exact mechanisms are still elusive [63] Since in vitro studies (cited above) have confirmed the antimicrobial efficacy of EOs, they can be used as natural growth promoters in livestock nutrition, in particular in poultry and pig farming [6]. Essential oils enhance the flavor and palatability of feeds, in particular those deficient in these attributes, which improves feed intake.…”
Section: Feed and Water Supplementation With Essential Oilsmentioning
confidence: 99%
“…The results of different studies analyzing the effects of dietary supplementation with EOs or their active ingredients on the health status and performance of animals are presented by many authors [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Feed and Water Supplementation With Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation